Penerapan Pembelajaran Qurma (Qur’an Dan Makna) untuk Meningkatkan Keterampilan Berbicara Siswa di MIN 3 Labuhanbatu - Sifa Khairunnisa Ritonga; Abdul Sattar Daulay; Nursyaidah Nursyaidah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
The background of this research is the condition where students‘ speaking skills are low in class IV A Madrasah Ibtidaiyah Negeri 3 Labuhanbatu. Based on observation data, students’ speaking skills in class IV A Madrasah Ibtidaiyah Negeri 3 Labuhanbatu are below 25%. Therefore, qurma learning is one of the solutions to improve students' speaking skills. Qurma learning is a process of interaction between students, teachers, and learning resources directly in a learning environment, where this learning process teaches students to be able to understand the meaning or content of the Qur'an by getting to know the stories that are in it. Speaking skills play a very important role in elementary school. Speaking skills are mechanistic, meaning that speaking skills are acquired through a process of continuous practice. So, as much practice as possible will make students skilled in speaking. Fostering speaking skills in students can be done through the qurma learning process (qur'an and meaning). Qurma learning is done by familiarising and training students to be skilled in telling stories related to the meaning of the Qur'an. The purpose of this study is to determine whether there is an improvement in students' speaking skills by using qurma learning in class IV A Madrasah Ibtidaiyah Negeri 3 Labuhanbatu. This research is a Classroom Action Research (PTK) using the Kurt Lewin model which contains the stages of planning, action, observation, and reflection. The data collection instruments used in this study were observation, interviews, documentation and tests. The results obtained by the researcher show that the application of qurma learning (qur'an and meaning) at Madrasah Ibtidaiyah Negeri 3 Labuhanbatu has increased from pre-cycle 25% or around 7 students who passed to 83% or 23 students who passed at the end of the meeting with the focus of habituation carried out such as telling the meaning contained in the Qur'an. Aiming for students to be able to convey with their own language orally or in writing. The implementation of qurma learning includes planning, implementation and evaluation of learning. The growth of speaking skills in students through qurma learning is characterised by the selection of words that are easy to understand, intonation placement, fluency, accuracy of speech and self-confidence.